Use and Trade of Bear Body Parts: Impact and Conservation in Arunachal Pradesh State of India - Sethy, Janmejay; Chauhan, N. P. S. (International Journal of Bio-resource and Stress Management, 2023)
The trade of bear and its body parts for use in traditional medicines, in cuisine, and as pets is widespread in Arunachal Pradesh State of India. The bile from bear gallbladder is an especially coveted medicine in the State where it is used to treat a variety of serious ailments. Bear paws are considered as a ‘tonic’ and a gourmet delicacy. Current level of trade in bear and bear parts, coupled with ongoing habitat loss throughout Asia, suggests a continuing decline in the sun bear (Helarctos malayanus) and the Asiatic black bear (Ursus thibetanus). Bears are protected in India and neighboring countries. During the survey (2007-2009) we recorded (n=701) bear parts, representing a minimum of (n=99) individual of both bear species. Most items were from Asiatic black bear. There were significant temporal and spatial differences in what items were offered for sale. Prices were low (US 4-40 item-1) and the total monetary value of the items for sale was USD ,500-5,500 (including gall bladder). Carcasses, skulls, canines, paws, claws, whole skins, pieces of skin, gall bladders and derivates, were openly displayed, with vendors being frank about prices, origin, and potential buyers.